Challenges and Impacts of the Absence of Public Libraries in Rural South Africa - Mashilo, Sedume; Mdhlalose, Dickson Scotch; Schellnack-Kelly, Isabel (Insaniyat : Journal of Islam and Humanities, 2025)
This study examines the effects of a rural community's lack of a public library. Access to reliable and relevant information is essential for making informed decisions towards achieving educational and developmental goals. Public libraries contribute to social and economic development by offering information vital for informed participation in societal activities, including access to opportunities. The study employed a qualitative research method, with fifty participants selected through purposive sampling from various categories within the rural areas surrounding Kwa-Mhlanga, Mpumalanga South Africa. Data were collected through structured interviews and focus groups and then analysed using thematic analysis. The study found a significant need for a public library in the rural areas surrounding Kwa-Mhlanga. The lack of access to information, education, and support materials negatively affects the community’s educational, social, cultural, and economic well-being. Based on this finding, the study recommends the establishment of a well-resourced, maintained and regularly updated public library to meet the information needs of the different populations that make up the community. Villages surrounding Kwa-Mhlanga should form a community group to promote the establishment of a public library or library services, collaborate with local schools to improve library resources and encourage community use after school hours and collaborate with local organizations to create a mobile library that transports books and resources to various community locations.